Pubertal fenvalerate exposure impairs cognitive and behavioral development partially through down-regulating hippocampal thyroid hormone receptor signaling. (10th October 2020) - Yang, Yang; Zhan, Feng; Wang, Ye-cheng; Wang, Bo; Shi, Meng-xing; Guo, Ce; Xu, De-xiang; Meng, Xiu-hong
Highlights: Pubertal exposure to low-dose fenvalerate causes neuronal damage in hippocampus. Pubertal exposure to low-dose fenvalerate impairs cognitive and behavioral development in a gender-dependent manner. Hippocampal thyroid hormone receptor signaling may be involved in fenvalerate-induced neurobehavioral impairment. Abstract: Fenvalerate, a synthetic pyrethroid insecticide, is an environmental endocrine disruptor and neurodevelopmental toxicant. An early report found that pubertal exposure to high-dose fenvalerate impaired cognitive and behavioral development. Here, we aimed to further investigate the effect of pubertal exposure to low-dose fenvalerate on cognitive and behavioral development. Mice were orally administered with fenvalerate (0.2, 1.0 and 5.0 mg/kg) daily from postnatal day (PND) 28 to PND56. Learning and memory were assessed by Morris water maze. Anxiety-related activities were detected by open-field and elevated plus-maze. Increased anxiety activities were observed only in females exposed to fenvalerate. Spatial learning and memory were damaged only in females exposed to fenvalerate. Histopathology observed numerous scattered shrinking neurons and nuclear pyknosis in hippocampal CA1 region. Neuronal density was reduced in hippocampal CA1 region of fenvalerate-exposed mice. Mechanistically, hippocampal thyroid hormone receptor (TR)β1 was down-regulated in a dose-dependent manner in females. In addition, TRα1 was declined only in females exposed to 5.0 mg/kg fenvalerate. Taken together, these suggests that pubertal exposure to low-dose fenvalerate impairs cognitive and behavioral development in a gender-dependent manner. Hippocampal TR signaling may be, at least partially, involved in fenvalerate-induced impairment of cognitive and behavioral development.